Causes of hospital admission among people living with HIV worldwide: a systematic review and meta-analysis. Issue 10 (October 2015) - Ford, Nathan; Shubber, Zara; Meintjes, Graeme; Grinsztejn, Beatriz; Eholie, Serge; Mills, Edward J; Davies, Mary-Ann; Vitoria, Marco; Penazzato, Martina; Nsanzimana, Sabin; Frigati, Lisa; O'Brien, Daniel; et al.
Summary: Background: Morbidity associated with HIV infection is poorly characterised, so we aimed to investigate the contribution of different comorbidities to hospital admission and in-hospital mortality in adults and children living with HIV worldwide. Methods: Using a broad search strategy combining terms for hospital admission and HIV infection, we searched MEDLINE via PubMed, Embase, Web of Science, LILACS, AIM, IMEMR and WPIMR from inception to Jan 31, 2015, to identify studies reporting cause of hospital admission in people living with HIV. We focused on data reported after 2007, the period in which access to antiretroviral therapy started to become widespread. We estimated pooled proportions of hospital admissions and deaths per disease category by use of random-effects models. We stratified data by geographical region and age. Findings: We obtained data from 106 cohorts, with reported causes of hospital admission for 313 006 adults and 6182 children living with HIV. For adults, AIDS-related illnesses (25 119 patients, 46%, 95% CI 40–53) and bacterial infections (14 034 patients, 31%, 20–42) were the leading causes of hospital admission. These two categories were the most common causes of hospital admission for adults in all geographical regions and the most common causes of mortality. Common region-specific causes of hospital admission included malnutrition and wasting, parasitic infections, and haematological disorders in the Africa region; respiratory disease, psychiatric disorders, renal disorders, cardiovascular disorders, and liver disease in Europe; haematological disorders in North America; and respiratory, neurological, digestive and liver-related conditions, viral infections, and drug toxicity in South and Central America. For children, AIDS-related illnesses (783 patients, 27%, 95% CI 19–34) and bacterial infections (1190 patients, 41%, 26–56) were the leading causes of hospital admission, followed by malnutrition and wasting, haematological disorders, and, in the African region, malaria. Mortality in individuals admitted to hospital was 20% (95% CI 18–23, 12 902 deaths) for adults and 14% (10–19, 643 deaths) for children. Interpretation: This review shows the importance of prompt HIV diagnosis and treatment, and the need to reinforce existing recommendations to provide chemoprophylaxis and vaccination against major preventable infectious diseases to people living with HIV to reduce serious AIDS and non-AIDS morbidity. Funding: None.